The EU Single Market: The value of membership versus access to the UK - Carl Emmerson; Paul Johnson; Ian Mitchell (Institute for Fiscal Studies (IFS), 2016)
On 23 June 2016, the UK public voted in favour of leaving the European Union. However, important decisions remain about the model for the UK's relationship with Europe outside of the EU, not least whether the UK seeks to remain a "member" of the Single Market or only seeks (tariff-free) "access". This report looks at exactly what the Single Market is and distinguishes between "membership" and "access", including the impact on the financial services sector. It also considers the potential for new trade deals beyond the EU and assesses the economic and public finance implications of the various options. This should inform the likely trade-offs between the level of access to the Single Market and other negotiating objectives such as control of immigration and budgetary contributions.
Keywords: 330